Implementation of Recovery Programming on an Inpatient Acute Psychiatric Unit and Its Impact on Readmission. Issue 2 (April 2016) - Koval, Renee D.; Mcdonagh, James; Grubaugh, Anouk; Young, Wendy; Corcoran, Beth; Lee, Angela; Dumas, Bonnie; Edlund, Barbara
Abstract: Background: Recovery-oriented models of care are evidence based and have been shown to improve patient satisfaction and outcomes as well as decrease the percentage of readmissions to inpatient psychiatric units. Methods: This quality improvement project was implemented on a 16-bed inpatient adult mental health unit in a Veterans Affairs Medical Center. Percentages of readmissions were compared throughout the course of implementation of the recovery model. Readmissions during the months of July–September were tabulated over 3 subsequent years and compared readmission percentages before recovery implementation, during the early stage of recovery implementation, and finally, during ongoing recovery implementation. Results: A decrease in readmission percentages was seen with implementation of recovery-oriented care when comparing the same 3-month period over 3 years. Conclusion: After implementation of recovery-oriented care measures, there was a decrease in percentage of readmissions to the unit. In addition, this decrease was sustained and was shown to improve over time as recovery-oriented programming was further developed on the unit. These data suggest that Veterans Affairs Medical Centers should consider adding tools and procedures to successfully implement recovery programming on inpatient units and efforts should include direct involvement of patients in their own recovery journey, revision of policies and procedures to reflect the importance of recovery, thorough training of frontline staff regarding recovery principles, and transfer of recovery information directly from inpatient units to outpatient providers.